The Impact of Gadget Utilization in Learning for Third Grade Students at SDN Inpres 6/84 Walehunian Sagerat - Agnes M. Rumagit; Widdy Harce Frans Rorimlpandey; Deitje Katuuk (Institut of Shanti Bhuana, 2024)
This research aims to determine the impact of using gadgets in learning for Grade 3 students at SDN Inpres 6/84 Walehunian Sagerat. This research method uses a qualitative research method which is research with an inductive mindset, namely a theory based on data and does not use statistics such as tables, graphs, diagrams and so on and is able to interact directly with the objects being researched. The place where this research was carried out was SDN Inpres 6/84 Walehunian Sagerat. The data collection techniques used in this research are: Observation, Interviews and Documentation. From the results of research conducted by researchers, it was found that the average age of children who have used these gadgets is from 2 years, 5 years, 7 years and so on, and it has been found that currently several students are addicted to using gadgets. Thus, it can be concluded that learning outcomes do not decrease due to the use of gadgets by reducing the duration of gadget use in a day.